2013
DOI: 10.7874/kja.2013.17.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Labyrinthine Concussion

Abstract: Background and ObjectivesInner ear symptoms like hearing loss, dizziness or tinnitus are often developed after head trauma, even in cases without inner ear destruction. This is also known as labyrinthine concussion. The purpose of this study is to determine the clinical manifestations, characteristics of audiometry and prognostic factors of these patients.Materials and MethodsWe reviewed the medical records of the 40 patients that had been diagnosed as labyrinthine concussion from 1996 to 2007. We studied the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 10 publications
2
24
0
Order By: Relevance
“…With an increasing recognition of the prevalence of cognitive, behavioral, and vestibular effects of sports-related concussion as well as traumatic brain injury, an auditory and vestibular evaluation should be added to the clinical care of these patients. 70,71 Sudden Sensorineural Hearing Loss Sudden SNHL is a well-reported occurrence in adults but little studied in children. Although the definition of idiopathic sudden SNHL includes unilateral onset, many subjects with sudden onset of SNHL actually have bilateral findings.…”
Section: Head Traumamentioning
confidence: 99%
“…With an increasing recognition of the prevalence of cognitive, behavioral, and vestibular effects of sports-related concussion as well as traumatic brain injury, an auditory and vestibular evaluation should be added to the clinical care of these patients. 70,71 Sudden Sensorineural Hearing Loss Sudden SNHL is a well-reported occurrence in adults but little studied in children. Although the definition of idiopathic sudden SNHL includes unilateral onset, many subjects with sudden onset of SNHL actually have bilateral findings.…”
Section: Head Traumamentioning
confidence: 99%
“…Concomitant audiological symptoms appeared to be associated with a poorer prognosis in our patients although the difference was not significant. A study has reported that hearing disturbance after head trauma improved less when dizziness was present [11] . This may be because the damage to the labyrinthine or inner ear is greater in patients with dizziness and concomitant hearing symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Labyrinthine concussion is also a common cause of post traumatic dizziness [5,11] . This disorder is thought to be caused by non-specific injury to the labyrinth.…”
Section: Discussionmentioning
confidence: 99%
“…According to Choi et al, they found that the hearing improved patients after head injury had obtained hearing gain mostly in low frequencies rather than high frequencies. 4 Their speculated mechanism was the vibrating wave affecting the basal turn of cochlea most severely, thus causing irreversible damage to the organ of Corti in the basal turn. Labyrinthine concussion can be confirmed mainly by audiometric tests.…”
Section: Discussionmentioning
confidence: 99%